Non-financial determinants influencing Sustainable Development Goals disclosure in traditional banking institutions in Latin America - Raffaelli, Pablo (Universidad ESAN, 2025)
Purpose: This paper examines the non-financial determinants influencing Sustainable Development Goals (SDGs) disclosure among Latin American banks. Design/methodology/approach: The study employs an explanatory methodological approach characterized by quantitative analysis and a longitudinal perspective. It applies a multiple linear regression model to examine the non-financial determinants influencing SDG compliance among banks listed on the national stock exchanges of the six Latin American countries with the highest nominal GDP in USD (World Bank, 2022). This group includes the four members of the Pacific Alliance (Chile, Colombia, Mexico, and Peru), along with Brazil—the only Latin American member of the BRICS—and Argentina, recognized for its significance in South America and its membership in the Group of Twenty (G-20). Findings: The findings reveal a direct and significant relationship between three variables of interest and financial institutions' disclosure of priority SDGs: board member independence, adherence to International Integrated Reporting Council guidelines in reporting, and the audit of sustainability reports by one of the Big Four firms. The variables of board size and the proportion of female employees exhibited a notable inverse relationship. Originality/value: This study provides empirical evidence from the Latin American context, advancing research on non-financial determinants in the sustainability reporting of financial services, and underscoring banks' commitment to sustainable development.
Keywords: Banks; Latin America; Sustainability reporting; SDG; Sustainability; Bancos; América Latina; Informes de sostenibilidad; ODS; Sostenibilidad; https://purl.org/pe-repo/ocde/ford#5.02.04